DESIGN OF AN INTER-AGENCY COLLABORATION MANAGEMENT INFORMATION SYSTEM USING A WEB-BASED PRIORITY SCHEDULING METHOD - Agustiah, Nita; Andika, Erick (SEMNASTERA (Seminar Nasional Teknologi dan Riset Terapan), 2025)
Collaboration between institutions at Politeknik Sukabumi is an important strategy to improve the quality of education, research, and community service. However, the administrative process, which is still carried out manually, causes several obstacles, such as difficulties in determining priorities, lengthy verification processes, and a lack of information transparency. To address these issues, a Web-Based Information System for Inter-Institutional Collaboration Management was developed by applying the Priority Scheduling method to determine the priority order of collaboration activities.This method evaluates priorities based on criteria of urgency, benefits, implementation duration, and availability of human resources, and is equipped with an automatic email notification feature to provide real-time updates on activity progress. The system was developed using a structured development approach with the Laravel framework, through the stages of needs analysis, design, implementation, and testing.The Black Box Testing results show that all system functions operated as expected. The priority determination process produced activity orders that were 100% consistent with manual assessments and was able to increase effectiveness by up to 93% compared to manual processes, reducing processing time from 7 days to 0.5 days.